2006
DOI: 10.1002/pmic.200600056
|View full text |Cite
|
Sign up to set email alerts
|

Parallel protein and transcript profiles of FSHD patient muscles correlate to the D4Z4 arrangement and reveal a common impairment of slow to fast fibre differentiation and a general deregulation of MyoD‐dependent genes

Abstract: Here, we present the first study of a human neuromuscular disorder at transcriptional and proteomic level. Autosomal dominant facio-scapulo-humeral muscular dystrophy (FSHD) is caused by a deletion of an integral number of 3.3-kb KpnI repeats inside the telomeric region D4Z4 at the 4q35 locus. We combined a muscle-specific cDNA microarray platform with a proteomic investigation to analyse muscle biopsies of patients carrying a variable number of KpnI repeats. Unsupervised cluster analysis divides patients into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 91 publications
13
95
1
Order By: Relevance
“…The absence of FRG2 on the disease alleles in some FSHD patients with a proximal deletion makes this gene a less attractive candidate gene [39] . However, transcriptional deregulation of these candidate genes in patients with FSHD is still under debate, as several studies showed contradictory results [22,[40][41][42][43] . Based on our data showing that hypomethylation is restricted to the D4Z4 repeat and not spreading in a proximal direction in addition to previous data showing no change in the chromatin structure of proximal sequences in FSHD [22] , we do not support a cisspreading mechanism emanating from D4Z4 in FSHD.…”
Section: D4z4 Hypomethylation Is Restricted To the D4z4 Repeat Arraymentioning
confidence: 99%
“…The absence of FRG2 on the disease alleles in some FSHD patients with a proximal deletion makes this gene a less attractive candidate gene [39] . However, transcriptional deregulation of these candidate genes in patients with FSHD is still under debate, as several studies showed contradictory results [22,[40][41][42][43] . Based on our data showing that hypomethylation is restricted to the D4Z4 repeat and not spreading in a proximal direction in addition to previous data showing no change in the chromatin structure of proximal sequences in FSHD [22] , we do not support a cisspreading mechanism emanating from D4Z4 in FSHD.…”
Section: D4z4 Hypomethylation Is Restricted To the D4z4 Repeat Arraymentioning
confidence: 99%
“…It has been also postulated that reduction of D4Z4 might have a more genome-wide effects, affecting other pathways, such the slow-to-fast fiber differentiation pathway (Celegato et al, 2006) and the response to oxidative stress and myogenic differentiation pathway (Winokur et al, 2003b). Because D4Z4 can be regarded as a docking platform for protein factors, loss of repeats may generate a local imbalance in the availability of D4Z4 proteins in the cell, and/or lead to new interaction with different proteins at the disease allele.…”
Section: Trans-effect Model: Genome Wide Effectmentioning
confidence: 99%
“…Many genes in this intersection have been associated with FSHD, e.g. TP53 [16], JUNB [20,17], HIF1A [20], WNT3 [4], LMO3 [20], ANXA4 [5] and HSPB1 [22]. Gene Set Enrichment Analysis (GSEA) [23] on the intersection also implicated many FSHD associated processes, such as myogenesis [17] and regulation of the actin cytoskeleton [15], and pathways, including, p53 [16], Wnt [4], and VEGF [5] To identify genes implicated as rewiring specifically in FSHD, we also ran InSpiRe on two datasets each describing skeletal muscle gene expression during ageing (GSE5086 [24] and GSE9676 [25]), disuse atrophy (GSE5110 [26] and GSE8872 [27]) and other muscle diseases involving inflammation and wasting (GSE3307 [19], where juvenile dermatomyositis and limb-girdle muscular dystrophy type 2A datasets were independently analysed).…”
Section: Meta-analysis Of Facioscapulohumeral Muscular Dystrophy Datamentioning
confidence: 99%